Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.ppat.1010187
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus type 2 (AAV2) uncoating is a stepwise process and is linked to structural reorganization of the nucleolus

Abstract: Nucleoli are membrane-less structures located within the nucleus and are known to be involved in many cellular functions, including stress response and cell cycle regulation. Besides, many viruses can employ the nucleolus or nucleolar proteins to promote different steps of their life cycle such as replication, transcription and assembly. While adeno-associated virus type 2 (AAV2) capsids have previously been reported to enter the host cell nucleus and accumulate in the nucleolus, both the role of the nucleolus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…S6 in the supplemental material). However, the image-based quantification of the post-transcriptional silencing of IFI16 revealed that neither partial uncoating in the cytoplasm, complete uncoating in the nucleolus, or cell cycle progression (32) was affected (data not shown).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…S6 in the supplemental material). However, the image-based quantification of the post-transcriptional silencing of IFI16 revealed that neither partial uncoating in the cytoplasm, complete uncoating in the nucleolus, or cell cycle progression (32) was affected (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…6, B and D). The DAPI based cell cycle analysis workflow was adapted from the protocol published by Roukos et al, 2015 (31) and validated as described previously (32). Both assays revealed an increase in the number of cells in G2 cell cycle phase upon AAV2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of co-release of larger molecules during parvovirus endosomal escape indicates that the virus-induced membrane rupture is limited and does not involve complete lysis (43). Specific to AAV2, it was demonstrated that the pH-dependent conformational changes of the AAV2 capsid results in the exposure of PLA 2 and is important for AAV2 infection, partial uncoating (45), endosomal escape (14), and nuclear entry in particular (46). However, inflicting endocytic membrane damage results either in a galectin-mediated membrane damage response pathway or in the induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…29 Inside the nucleus, the AAV capsid uncoats releasing the single-stranded DNA (ssDNA) genome. 30 The ssDNA genome is converted to a double-stranded intermediate by the host cell's DNA repair machinery, which then circularizes via the ITRs. 31 These circular AAV genomes are known as "episomes," a stable non-integrating form of the viral cargo that can exist as circular monomers or concatamers.…”
Section: Transduction Of Liver With Raav Vectorsmentioning
confidence: 99%
“…Next, basic clusters in VP1 and VP2 subunits act as nuclear localization sequences to direct the AAV capsid into the nucleus 29 . Inside the nucleus, the AAV capsid uncoats releasing the single‐stranded DNA (ssDNA) genome 30 . The ssDNA genome is converted to a double‐stranded intermediate by the host cell's DNA repair machinery, which then circularizes via the ITRs 31 .…”
Section: Transduction Of Liver With Raav Vectorsmentioning
confidence: 99%